An application of NPD to double-stage diamond anvil cells: XAS spectra of rhenium metal under high pressures above 300 GPa. Issue 1 (2nd January 2020) - Kuramochi, K.; Ishimatsu, N.; Sakai, T.; Kawamura, N.; Irifune, T.
ABSTRACT: We present the first application of double-stage diamond anvil cells (ds-DACs) to X-ray absorption spectroscopy (XAS) of Rhenium (Re) metal. By using highly stable and sub-micron sized X-ray beam, XAS spectra were successfully observed at the L 2, 3 -edges from the sample encapsulated in the small space between the second-stage anvils. The pressure generation exceeding 300 GPa was evaluated by the pressure-induced shift of extended X-ray absorption fine structure (EXAFS) oscillation at the L 3 -edge. The profile of white-line at the L 2, 3 -edges broadened with increasing pressure, which indicates the modification of the Re 5 d band structure. The present results demonstrate the high ability of XAS technique combined with ds-DACs as a probe for crystal structure and electronic structure under ultrahigh pressure.